PENGARUH MOTIVASI KERJA DAN TOTAL QUALITY CONTROL (TQC) TERHADAP KINERJA KARYAWAN (Studi Kasus PT.Sansyu Precision Indonesia) - Chusnah, Chusnah; Khoridah, Lulu Arifatun (Kinerja, 2021)
PT. Sansyu Precision Indonesia is a manufacturing company engaged in injection molding. This study aims to determine the effect of work motivation and total quality control on employee performance.The sample used in this study were permanent employees as many 65 respondents with a purposive technique. The data analysis method used is regression and hypothesis testing.Based on the results of data analysis and hypothesis testing, it is known that work motivation and total quality control have a positive and significant effect on employee performance at PT. Sansyu Precision Indonesia. The amount of influence given by the variable Work Motivation and Total Quality Control on Employee Performance is 56.4% while the remaining 43.6% is influenced by other variables which are not researched or discussed in this study.